Pendekatan Holistik pada Perempuan Usia 29 Tahun dengan Kehamilan dan Anemia Melalui Pendekatan Kedokteran Keluarga di Puskesmas Rajabasa Indah - Siregar, Kenos Stefanus; Nusadewiarti, Azelia (Medula, 2025)
Anemia remains a significant health concern, particularly among pregnant women, despite existing intervention efforts. Its prevalence is influenced by several risk factors, including inadequate iron intake, leading to iron deficiency anemia. A holistic approach is necessary to manage anemia effectively during pregnancy. This case report aims to identify the risk factors and clinical condition of a pregnant patient in order to provide comprehensive management that is patient-centered, family-focused, and community-oriented. The subject of this case is Mrs. A, a 29-year-old woman who was five weeks pregnant and presented with fatigue and dizziness for approximately one month. The diagnosis of iron deficiency anemia was made, and her condition was classified as functional class II. Both internal and external risk factors contributed to her clinical presentation. Management of her condition was carried out according to current theory and evidence-based medicine. The intervention focused not only on treating clinical symptoms but also on empowering the patient and her family to improve health behavior. A holistic approach in the treatment of disease is essential as it helps reduce risk factors by increasing patient awareness and encouraging sustainable lifestyle changes.